Masculinities as peer discourses: identities, school cultures and the resistance to power - Wilson, Rebecca Anne Jane (Curtin University, 2007)
This thesis examines peer influences on the development of masculinities for a group of boys attending a secondary school. A small male peer group in a selected school setting was studied over a three - year period, with an emphasis on extensive observation and interview. The study suggests that students actively engage in resistance as a way to claim power and prove masculinities, and thus identities, in the school setting, often resulting in poor educational outcomes for individual boys. The thesis proposes that discourses of masculinities are central to the creation of identities for young adolescent males, and shape the way they present as learners in the school environment. These discourses are informed and governed by peers and the need for individuals to find belonging within the peer milieu. Central to such discourses is the theme of power. Focused on gender as being socially constructed, and humans perceived to be self determining and moulded through interactions with others, this study is strongly influenced by the ideas of John Dewey (1910, 1966), Charles Taylor (1989, 1994) and Michael Foucault (1971,1977,1978,1981). It uses a framework based on three central themes - identity, power, and peer relationships, to shape and provide focus to the inquiry. In so doing, it seeks to find a "third space", a place where meanings become "fused" and "new horizons" emerge. The presentation is divided into four sections. The first section outlines the nature, research design and setting of the study. The second uses dialogue of the varying voices I brought to the research to explore the central themes of the framework. The third section draws the three themes together to examine the subjects' understanding of masculinities and how this influences their identities as learners, as well as how they perceive possible futures.The final section summarises the major findings and examines emerging possibilities that focus on hope for change, suggesting that by allowing students agency and voice there are opportunities for rich, open and authentic dialogue between educators and students. Through ongoing critical inquiry and analysis of gender and gender relations there is the possibility of new ways of being (Davies, 1997) resulting in improved learning outcomes for both boys and girls.